Envelhecimento e institucionalização: as experiências na Fundação Obras Sociais da Paróquia da Boa Viagem em Belo Horizonte - Vanja de Castro Juste (2009)
This study approaches the aging process in a social environment that is marked by serious political and economical issues, technological advancement, ones ephemeral image and also by the new ways to perceive reality after industrialization, causing significant transformations in lifestyle and everyday routine of relationships and creating adding more complexity to the lives of elderly people. Entering an Assisted Living Facility (ILPI) becomes an alternative that appears to be a solution for the situation which families, society and elderly people themselves are facing nowadays. It clearly shows, according to the strategy for people redistribution into categories, the effect of the social mechanisms to manage life, which are a characteristic of bio-politics of populations. The investigation of the effects caused by these mechanisms becomes relevant especially because of the way old age is conveyed. The contexts of two ILPIs (Assisted Living Facilities) located in the city of Belo Horizonte, state of Minas Gerais were here presented; the different lifestyles experienced in these environments were described and analyzed as well as life trajectories and situations that might have favored the decision of entering an ILPI; in addition, the assisted livings influence on the subjectivity of those who live in such facilities was also examined. One of the facilities accommodates twenty-seven women; the other has eighty-six residents. Eighteen elderly people of both genders were interviewed individually, mainly in 2008. The ethnographic approach served as basis for this study, and the following techniques were used: field observation, group work with development of different dynamics; interviews were guided by the story told and documental research, which also involved the ILPIs managers, and leaders of the zitas - housemaids that had the support of the Social Work sector of the Boa Viagem Parish (local Catholic church) to build a place where they could live in old age. Admission procedures showed normalizing and quantitative assessments, which were inadequate for an old person in need of shelter; and the triage was a bureaucratic mechanism. Both the spontaneous admission to an assisted living facility, that is, the one that derives from decision made by both the family members and the elderly person (and also by the external pressure), and the assisted living that is determined by the family members or employers, sometimes without the elderly persons own consent, were observed. The zitas experience a peculiar situation, that is, the planned assisted living. The increase of ILPIs makes it evident how complex the social phenomena are and how incipient the manners to assist elderly people are to efficiently contribute to the preservation of the original bonds.